Harder, better, faster, stronger: biochemistry and biophysics in the immunosurveillance concert. Issue 2 (February 2022) - Tello-Lafoz, Maria; de Jesus, Miguel M.; Huse, Morgan
Abstract : Antitumor immunosurveillance is triggered by immune cell recognition of characteristic biochemical signals on the surfaces of cancer cells. Recent data suggest that the mechanical properties of cancer cells influence the strength of these signals, with physically harder target cells (more rigid) eliciting better, faster, and stronger cytotoxic responses against metastasis. Using analogies to a certain electronic music duo, we argue that the biophysical properties of cancer cells and their environment can adjust the volume and tone of the antitumor immune response. We also consider the potential influence of biomechanics-based immunosurveillance in disease progression and posit that targeting the biophysical properties of cancer cells in concert with their biochemical features could increase the efficacy of immunotherapy. Highlights: Immune responses are canonically triggered by biochemical signals. Many immunoreceptors, however, are mechanosensitive, and thus rely on the mechanical forces generated at cell-to-cell contacts to achieve full signaling capacity. Materials that mimic the mechanical properties of cells are useful for delineating the contribution of biophysical inputs to immune activation. As with all artificial systems, however, results must be interpreted with care. Mechanotransduction is particularly relevant for cytotoxic lymphocyte responses against metastatic cancer cells. As such, cytoskeletal regulators such as myocardin-related transcription factors (MRTFs) might serve as prognostic markers and targets for immune checkpoint blockade (ICB) therapy. Small-molecule therapies can induce mechanical reprogramming of tumor cells and elicit resistance mechanisms. In these cases, targeting emergent biophysical vulnerabilities of the tumor with immunotherapy might improve treatment outcomes.